2013
DOI: 10.2967/jnumed.112.110825
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Assessment of In Vivo Metabolism with Hyperpolarized [1-13C]MR Spectroscopy and 18F-FDG PET Imaging in Hepatocellular Carcinoma Tumor–Bearing Rats

Abstract: Abnormalities of tumor metabolism can be exploited for molecular imaging. PET imaging of 18 F-FDG is a well-established method using the avid glucose uptake of tumor cells. 13 C MR spectroscopic imaging (MRSI) of hyperpolarized [1-13 C]pyruvate and its metabolites, meanwhile, represents a new method to study energy metabolism by visualizing, for example, the augmented lactate dehydrogenase activity in tumor cells. Because of rapid signal loss, this method underlies strict temporal limitations, and the acquisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 34 publications
2
60
0
Order By: Relevance
“…Only preclinical comparisons have been performed and that being on separate PET and MR systems (25,26), with potential errors arising from the time difference between the examinations and the repositioning of the animal. Admittedly, it may not be with 18 F-FDG that the time difference is the largest challenge but with other potential PET tracers to be combined with CSI.…”
Section: Discussionmentioning
confidence: 99%
“…Only preclinical comparisons have been performed and that being on separate PET and MR systems (25,26), with potential errors arising from the time difference between the examinations and the repositioning of the animal. Admittedly, it may not be with 18 F-FDG that the time difference is the largest challenge but with other potential PET tracers to be combined with CSI.…”
Section: Discussionmentioning
confidence: 99%
“…There was no attempt to correlate 18 F FDG uptake and 13 C MRS across animals in the abovementioned studies. In a study of hepatocellular carcinoma tumor-bearing rats [17], tumors exhibited increased 18 F FDG uptake and locally increased pyruvate-to-lactate exchange. However, no correlation between PET and MRS data was observed across animals, possibly corresponding to the lack of correlation we observe for the canine carcinoma patients.…”
Section: Tablementioning
confidence: 99%
“…Group differences of [1- Only a few earlier studies have compared 18 F FDG PET and hyperpolarized [1-13 C]pyruvate MRS in animal models [16,17], and using sequential exams as opposed to simultaneous exams performed by us in the combined PET/MR clinical system. In a study of murine lymphoma treatment [16], a comparable decrease in 18 F FDG uptake and pyruvateto-lactate exchange was found 24 h after chemotherapy, with the decrease in 18 F FDG uptake appearing earliest.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Direct comparison of diagnostic accuracy of 11 C-acetate or 18 F-fluorocholine PET/CT versus hepatocyte-specific MRI on liver tumors would be of great interest; this area of research is still under investigation. Menzel et al recently reported a multimodal in vivo assessment of glucose metabolism in HCC tumors using hyperpolarized [1- 13 C]pyruvate DNP-MRS and 18 F-FDG PET [138]. The increased [1- 13 C]lactate signals in the tumor is correlated with corresponding enhanced 18F-FDG uptake.…”
Section: Positron Emission Tomography (Pet)mentioning
confidence: 99%